The local communities' perceptions on the role and benefits of tourism in the protected areas: a case of the Kruger National Park. - Khashane, Rofhiwa Stein (Vaal University of Technology, 2019)
Tourism is poised to play a greater role than ever before in terms of job creation, empowerment and economic growth, both on the global stage and in South Africa. In 2011, the tourism sector worldwide supported 258 million direct, indirect and induced employment opportunities. Community participation should be considered necessary to obtain community support, and the acceptance of tourism development projects, in addition, helps to ensure that the benefits (employment and/or entrepreneurships) are related to the local community’s needs. The main aim of the current study was to analyse the local communities’ perceptions of the role and benefits of tourism in the protected areas concerned. The analysis was approached on the basis of surveying the local communities concerned. The quantitative approach adopted as the chosen research method ensured that the required descriptive statistics could be derived from the research material available. A non-probability sampling approach was used to collect the data involved. The study was conducted in two villages, Ka-Mhinga and Ka-Matiani, adjacent to the Kruger National Park. Based on the results obtained, the surveyed community members of Ka-Mhinga and Ka- Matiani were found to share similar perceptions regarding the broader communities’ participation in, and decision-making control of the tourism operations in the area. The female participants agreed significantly more strongly than did the male participants concerning which aspects impeded an appreciation of the benefits of tourism. Such agreement probably indicates that the female participants perceived themselves as being worse affected by tourism than were the male participants. The participants from the two villages who perceived themselves as being excluded from the managerial decisions taken agreed significantly more strongly with the exclusion factor than the participants who perceived themselves as having been included in the managerial decisions taken regarding the protected areas. The results obtained in the present study indicate that the communities from the two villages receive minimal benefits from tourism. Some of the residents noted that they were not in receipt of what they had been promised when the Kruger National Park opened. The participants from the above-mentioned villages agreed that the locals were not employed in the protected area, and that the tourism goods which were sold at the Punda Maria information centre were not produced by the local residents, as well as that the Park’s management were influenced by nepotism in their employment of workers. The study concluded that an education and training budget should be provided by both the government and the protected areas. The involvement of the communities adjacent to the Kruger National Park in tourism planning would be likely to promote their participation in, and their beneficiation from, tourism. The community residents of Ka- Mhinga and Ka-Matiani should form part of the related control processes and decisio-nmaking, so as to improve the level of benefits obtained from tourism, which would enable them to enjoy the benefits of the Kruger National Park. Despite the study revealing the benefits of tourism gleaned by the two villages, engaging in an increased number of initiatives is likely to elicit even more benefits, with all the investors participating in the operation, execution, monitoring, and management of tourism activities as a form of collaboration.
M. Tech. (Department of Tourism and Hospitality Management, Faculty of Human Sciences), Vaal University of Technology.
Keywords: Tourism; Protected areas; Communities' roles and benefits; Tourism development; Kruger National Park; Dissertations, Academic -- South Africa; Tourism -- South Africa; National parks and reserves -- South Africa; Employment (Economic theory); Entrepreneurship